2021
DOI: 10.3390/md19060306
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Technologies for Highly Active Omega-3 Fatty Acids from Krill Oil: Clinical Applications

Abstract: Euphausia superba, commonly known as krill, is a small marine crustacean from the Antarctic Ocean that plays an important role in the marine ecosystem, serving as feed for most fish. It is a known source of highly bioavailable omega-3 polyunsaturated fatty acids (eicosapentaenoic acid and docosahexaenoic acid). In preclinical studies, krill oil showed metabolic, anti-inflammatory, neuroprotective and chemo preventive effects, while in clinical trials it showed significant metabolic, vascular and ergogenic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 152 publications
(171 reference statements)
0
18
0
Order By: Relevance
“…Krill oil has been associated with improvement of exercise and antioxidant/anti-inflammatory markers and several clinical trials have been carried out. A recent review by Colletti et al 2021 [ 60 ] details in great depth the aspects of krill oil actions on muscle performance and strength. One of the possible pathways is that krill oil activates mTOR signaling [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Krill oil has been associated with improvement of exercise and antioxidant/anti-inflammatory markers and several clinical trials have been carried out. A recent review by Colletti et al 2021 [ 60 ] details in great depth the aspects of krill oil actions on muscle performance and strength. One of the possible pathways is that krill oil activates mTOR signaling [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an excellent nutritional source of the essential nutrient choline and a broad range of various amino acids including essential amino acids. The content of the different classes of nutritional components is greatly influenced by the extraction technologies [ 60 , 78 ]. The exact percentage of each constituent was not disclosed to us by Rimfrost Inc. as that is patented information [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher bioavailability of krill oil can be correlated with other valuable antioxidant compounds, including astaxanthin, tocopherols, vitamin A, and flavonoids, and was reported to enhance the absorption efficacy in the gut, as well as in the brain [77]. Several previous in vivo and in vitro studies showed that krill oil exhibits anti-inflammatory, anti-obesity, and anti-diabetic effects, and could function to alleviate cardiovascular diseases and other illnesses [64,76]. However, the exact molecular mechanisms are still not well-elucidated.…”
Section: Marine Sourcesmentioning
confidence: 99%
“…Another interesting source is krill (Euphausia superba), a small marine crustacean from the Antarctic Ocean. It has received increased attention due to its nutraceutical potential and due to its high levels of lipids and phospholipids (39.29-80.69%), and for having a high content of (ω-3) PUFA, mainly represented by EPA and DHA [64,76]. It is important to point out that fish oil, including krill oil supplements, are different carriers of EPA and DHA.…”
Section: Marine Sourcesmentioning
confidence: 99%